Change resistance moderates existence and longevity biases. (2nd April 2016) - Shockley, Ellie; Rosen, Rebecca Kala; Rios, Kimberly
Abstract: Evidence has been found for existence and longevity biases—inferences of goodness from prevalence or longevity. We argue these biases actually emerge among change-resisting individuals. Our evidence suggests change-accepting individuals can even demonstrate a reversal of these biases. In two studies, change-resisting individuals' attitudes were suggestive of existence and longevity biases while change-accepting individuals significantly reversed this pattern by evaluating long-standing or prevalent objects less favorably. Finally, we reanalyzed data from the existence and longevity biases literature previously reported in Social Influence. We found Americans identifying as more Republican—thus theorized as more change-resisting—were those who favored a long-standing practice. Altogether, we argue that existence and longevity biases emerge depending on individuals' change resistance, indicating an important theoretical expansion.